Does Cyclic ADP-Ribose (cADPR) Activate the Non-selective Cation Channel TRPM2? - Fliegert, Ralf; Riekehr, Winnie M.; Guse, Andreas H. (Frontiers in Immunology, 2020)
TRPM2 is a non-selective, Ca2+-permeable cation channel widely expressed in immune cells. It is firmly established that the channel can be activated by intracellular adenosine 5′-diphosphoribose (ADPR). Until recent cryo-EM structures have exhibited an additional nucleotide binding site in the N-terminus of the channel, this activation was thought to occur via binding to a C-terminal domain of the channel that is highly homologous to the ADPR pyrophosphatase NudT9. Over the years it has been controversially discussed whether the Ca2+ mobilizing second messenger cyclic ADP ribose (cADPR) might also directly activate Ca2+ entry via TRPM2. Here we will review the status of this discussion.